Localization of Shear Waves in Inhomogeneous Periodically Stratified Waveguide - Ghazaryan, K.; Ghazaryan, R.; Terzyan, S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
For a special class of inhomogeneity materials this analytical study demonstrates localization of shear elastic wave in periodically stratified waveguide, consisting of periodically repeated perfectly bonded inhomogeneous identical finite number unit cells. For inhomogeneous material with periodic non symmetrical profiles is shown that due to inhomogeneity the shear guided waves can be localized at interfaces in the waveguide. The localization of waves significantly increases with the numbers of the waveguide unit cells. For inhomogeneous material with symmetrical profiles is shown that this material does not support localization in waveguide. Для определенного класса неоднородных материалов аналитически установлена возможность локализации сдвиговой упругой волны в слоистом волноводе, состоящем из периодически повторяющихся упруго контактирущих неоднородных конечнего числа идентичных слоев. Для неоднородного материала с периодическими несимметричными профилями показано, что вследствии неоднородности имеет место локализация сдвиговых волн на внешних границах волновода Локализация волн значительно усиливается с увеличением числа элементарных ячеек волновода. Для неоднородного материала с симметричными профилями показано, что в этом волноводе локализация сдвиговых волн не имеет место. Անհամասեռ նյութերի որոշակի դասի համար անալիտիկորեն հաստատված է շերտավոր ալիքատարում սահքի առաձգական ալիքի տեղայնացման հնարավորությունը։ Շերտավոր ալիքատարը բաղկացած է պարբերաբար կրկնվող, առաձգականորեն հպված վերջավոր թվով նույնական շերտերից։ Պարբերական, ոչ սիմետրիկ պրոֆիլներով անհամասեռ նյութի համար ցույց է տրված, որ անհամասեռության հետևանքով ալիքատարի արտաքին եզրերում տեղի ունի սահքի ալիքների տեղայնացում։ Ալիքատարի տարրական բջիջների թվի աճին զուգընթաց ալիքների տեղայնացումը զգալիորեն ուժեղանում է։ Սիմետրիկ պրոֆիլներով
Keywords: Mechanics